Effects of hard particles on friction coefficients and particle embedment in brake system during hard braking - Abdul Hamid, M.; Stachowiak, Gwidon; Syahrullail, S. (2012)
The effects of hard particles on the friction coefficients and particle embedment during hard braking were investigated. Silica sands grit of the size between 180 to 355 µm were used during the experiments. The results were compared to the results obtained without the grit particles present in order to determine the change in friction coefficient, the fluctuation of frictional oscillation amplitude, and the percentage of particle embedment. Different sliding speeds were applied to investigate the relationship between particle embedment with friction coefficient and friction oscillation amplitude. Presence of hard particles of different grit size is found to significantly affect the friction coefficient and standard deviation of friction oscillation amplitude values. The friction coefficient and standard deviation values of friction oscillation amplitude increase with particle embedment due to the rapid changes of the effective contact area and the abrasion mode operating in the gap interface. Also, particle embedment tends to increase the disc surface roughness and influence the stopping time of the disc.